Phenotype and virulence assessment of a Burkholderia pseudomallei soil isolate from Malaysia - Wong, Rui-Rui; Khairom-Muslihin Baharom,; Ahmad-Kamal Ghazali,; Abdul Karim Russ Hassan,; Sheila Nathan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Burkholderia pseudomallei, a Gram-negative soil saprophyte, is the causative agent of life-threatening melioidosis. B. pseudomallei from soil and water remains a common source of human and animal infection via skin abrasions, ingestion or inhalation. Despite the reported sero-prevalence in healthy individuals among Malaysian rice farmers, there are limited reports on B. pseudomallei isolated from water or soil around the country. In this study, we characterized a B. pseudomallei soil isolate and compared it to local clinical isolates. 16s rRNA sequencing was adopted to confirm the identity of the soil isolate, NC20. B. pseudomallei NC20 colony morphology, in vitro growth rate and antibiotic sensitivity were examined and compared to two B. pseudomallei clinical isolates, UM6 and D286. Virulence properties such as biofilm formation and infection in a nematode host were also examined. The soil isolate NC20 exhibited distinguishable features of B. pseudomallei, comparable growth rate and similar antibiotic resistance profile to UM6 and D286. Additionally, NC20 is a medium-level biofilm producer with levels similar to D286, where the amount of biofilm produced was much less relative to UM6. Interestingly, NC20 exhibited weaker killing of the Caenorhabditis elegans infection model relative to the clinical isolates. The comparison between soil-derived and clinical isolates of B. pseudomallei demonstrated that both soil and clinical isolates shared certain phenotypic properties but the soil isolate was somewhat less virulent than the clinical isolates used in this study.